O rizoma bíblico-literário - Teixeira, Gismair Martins (2014)
This thesis aims to present, in an epistemological perspective and fictional, the relationship between the Bible and the Literature. Divided into two parts, this study includes first, an approach around the literary criticism, which has been focusing on the relationship between the biblical text and the universe of literary studies. Of the number of experts who have devoted their lives to studying it, we have selected two important names of the literary criticism international in the 20th century, that have stood on this interaction in perspective that we can say of complementary and rhizomatic as the postulates of epistemology proposed by Gilles Deleuz and Félix Guattari. They are the Canadian Northrop Frye and the American Harold Bloom. Of both, the latter is the one that more intensely established the dialog between the Jewish-Christian book and the Literature. From the intriguing conclusions of these theorists, we opened for a second time that establishes the relationship between the thoughts of these experts, with emphasis in Bloom, and the lusophone fiction of three Romanesque clippings: A mulher que escreveu a Bíblia, by Moacyr Scliar; Caim, by José Saramago and Grande sertão: veredas, by João Guimarães Rosa. These works are analyzed in inter-textual dialogs with other literary representations national and international, that include the relationship between the Bible and the Literature in an approach of hypertextuality of conceptualization by Gerard Genette, that in turn converses with considerations of Linda Hutcheon alluding to studies on the parody. As a methodology, we are employing the bibliographic research relating to the object of research relevant to the thesis. As a result of our research, we conclude that there is a plentiful cartography, that this work is an example, which contradict the existence of biblical-literary rhizome, which leads to the proposition that the Bible, one of the most important artistic codes of Western culture, it is a work that can be seen as a literary piece as advocates Harold Bloom, without prejudice of the rhizome that links it to the religiosity, working as one of the most intrigu ing hypo-texts of Western Literature, which can also be researched on a level of high erudition in his hypertextuality.